2016
DOI: 10.1177/2277978716671053
|View full text |Cite
|
Sign up to set email alerts
|

Taxable Capacity, Tax Efforts and Structural Break: Do the Child States Follow Their Respective Parents?

Abstract: The present article makes an attempt to test the hypothesis whether smaller states have better fiscal efficiency in terms of own tax revenue collections or not. This has been tested by taking the case of three states Uttar Pradesh, Madhya Pradesh and Bihar with their child states Uttarakhand, Chhattisgarh and Jharkhand, respectively. For this purpose tax buoyancy, tax capacity and efforts, and structural break models—Chow test (with known break points) and Quandt likelihood ratio (QLR) test (with unknown break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…States exploiting such low level of their own resources may not sustain. Maurya, Singh, and Khare (2016) observed that parent states do not perform any better than their child states in exploiting revenue potential. Garg, Goyal, and Pal (2017) estimate tax effort of Indian states using Stochastic Frontier Analysis in a panel data framework from 1991-1992 to 2010-2011.…”
Section: Some Past Studies On Indiamentioning
confidence: 98%
“…States exploiting such low level of their own resources may not sustain. Maurya, Singh, and Khare (2016) observed that parent states do not perform any better than their child states in exploiting revenue potential. Garg, Goyal, and Pal (2017) estimate tax effort of Indian states using Stochastic Frontier Analysis in a panel data framework from 1991-1992 to 2010-2011.…”
Section: Some Past Studies On Indiamentioning
confidence: 98%
“…Numerous Indian studies have calculated tax effort for states with an interest in assessing their relative tax performances (Nambiar and Rao ; Reddy ; Thimmaiah ; Sen and Tulasidhar ; Jha et al ; Coondoo et al ; Purohit ; Agarwal ; Karnik and Raju ; Maurya, Singh and Khare ; Garg, Goyal and Pal ). The two methods most frequently used in these studies are regression and the representative tax system (RTS) approaches.…”
Section: Reviewing the Relationship Between Central Transfer And Tax mentioning
confidence: 99%
“…A unifying theme in all the countries, as opposed to 'tax effort' and 'tax capacity' concepts, that are not used in this study. In the literature, often tax capacity is defined as the maximum (and/or predicted) potential level of tax revenue that a country can collect, whereas tax effort refers to the ratio between actual revenue and tax (or predicted total taxable) capacity (Garg, Goyal, Pal 2017;Maurya, Singh, Khare, 2016;Piancastelli, 2001).…”
mentioning
confidence: 99%